The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.analchem.8b02151
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-MSI of Immunotherapy: Mapping the EGFR-Targeting Antibody Cetuximab in 3D Colon-Cancer Cell Cultures

Abstract: Immunotherapies are treatments that use a patient's immune system to combat disease. One important type of immunotherapy employed in cancer treatments is the delivery of monoclonal antibodies to block growth receptors. In this manuscript, we develop a methodology that enables accurate and simple evaluation of antibody-type drug delivery using MALDI-MSI. To overcome the mass-range limitation that prevents the detection of large therapeutic antibodies, we used in situ reduction and alkylation to break disulfide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…The most common form of colon cancer is adenocarcinoma (Beloqui et al, 2016; Yueh et al, 2016), so we selected HT-29 adenocarcinoma cells as a colon cancer model. These cells are frequently used in tumorigenicity studies (Al-Saffar et al, 2018; Guerrero et al, 2018; Liu et al, 2018) and can form well-differentiated adenocarcinoma consistent with primary colon cancer in nude mice (Handali et al, 2018). We found PTX-CPT-P4C6 nanovesicles to suppress proliferation of HT-29 cells more than Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of colon cancer is adenocarcinoma (Beloqui et al, 2016; Yueh et al, 2016), so we selected HT-29 adenocarcinoma cells as a colon cancer model. These cells are frequently used in tumorigenicity studies (Al-Saffar et al, 2018; Guerrero et al, 2018; Liu et al, 2018) and can form well-differentiated adenocarcinoma consistent with primary colon cancer in nude mice (Handali et al, 2018). We found PTX-CPT-P4C6 nanovesicles to suppress proliferation of HT-29 cells more than Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix-assisted-laser-desorption-ionization mass-spectrometry imaging (MALDI-MSI) is a widely employed imaging technique that can visualize the spatial arrangement of drugs and metabolites in tissue from the whole-body level to the subcellular level [ 34 ]. In a proof-of-concept study, Liu et al demonstrated that a MALDI-MSI technique can detect and assess the distribution of cetuximab, an anti-EGFR monoclonal antibody, throughout colon cancer spheroids [ 35 ]. Since the MALDI-MSI technique can also be applied to tissue, it is feasible to identify optimal antibodies via a spheroid screening assay, then assess the best antibody candidate in vivo.…”
Section: Spheroidsmentioning
confidence: 99%
“…CTOs poorly retain immune cells usually and often require cocultures with immune cells (59). They could show that the diffusion and distribution of Cetuximab in 3D tumor models was similar to those occurring in vivo in previous studies (60). Organoids can be cultured in the presence of immune cells to assess their antitumoral activity as well as to test methods to stimulate them.…”
Section: Patient Derived 3d Modelsmentioning
confidence: 80%